EVALUASI EFEKTIVITAS PENGELOLAAN LABORATORIUM FISIKA DAN IMPLIKASINYA TERHADAP MINAT BELAJAR SISWA DI SMA BINA UTAMA I - Lestari Anggesia; Elia Ayu Wandira O’O; ,Ira Novita Sari (LPPM Universitas Cipta Mandiri, 2025)
This study aims to evaluate the effectiveness of Physics laboratory management at Bina Utama High School and its impact on students' interest in learning. This research uses descriptive evaluative method by collecting data through observation, interview, and documentation. The results showed that laboratory cleanliness is only maintained after practicum, while safety facilities such as personal protective equipment and emergency evacuation systems are not yet available. Equipment management is still manual with records that are rarely updated, and chemicals are stored with minimal safety standards. Practicum is often hampered by the lack of supervision and student involvement. Although there is a development plan, its implementation depends on limited BOS funds. Thisresearch highlights the need to improve laboratory management through innovative approaches to increase students' interest in learning and ensure safety during practicum. This evaluation is expected to be the basis for developing more effective laboratory management policies.